The molecular phylogeny and morphology revealed a new wood-rotting fungus Vararia yunnanensis (Peniophoraceae, Russulales) in Yunnan Province, China - Deng, Ying-Lian; Zhao, Chang-Lin (Phytotaxa, 2023)
Vararia yunnanensis sp. nov. is proposed based on a combination of morphological features and molecular evidence. Vararia yunnanensis is characterized by the resupinate basidiomata with a cracking hymenial surface, a dimitic hyphal system with generative hyphae bearing simple-septa, and colorless, slightly thick-walled, smooth, amyloid basidiospores measuring 5–12 × 3.5–9 µm. The phylogenetic analyses of ITS+nLSU in Russulales showed that V. yunnanensis nested into the family Peniophoraceae, in which V. yunnanensis grouped within the genus Vararia. Furthermore, the ITS sequence data indicated that the new species is sister to Vararia ellipsospora.